PP2A-Like Protein Phosphatase (Sit4) Regulatory Subunits, Sap155 and Sap190, Regulate Candida albicans’ Cell Growth, Morphogenesis, and Virulence - Han, Q. (Frontiers Media S.A., 2022)
10.3389/fmicb.2019.02943